Deep Brain Stimulation for Movement Disorders - Pizzolato, Gilberto; Mandat, Tomasz (Frontiers in Integrative Neuroscience, 2012)
Application of the stereotactic technique to neurosurgery and introduction of deep brain stimulation (DBS) were the milestones in surgical neuromodulation. Presently, the role of the DBS in the treatment of clinically and epidemiologically relevant movement disorders is widely accepted and DBS procedures are performed in many clinical centres worldwide. Here we review the current state of the art of DBS treatment for the most common movement disorders: Parkinson’s disease, essential tremor, and dystonia. In this review, we give a brief description of the candidate patient selection criteria, the different anatomical targets for each of these condition, and expected outcomes as well as possible side effects.